High-risk Human Papillomavirus Messenger RNA Testing in Wet and Dry Self-collected Specimens for High-grade Cervical Lesion Detection in Mombasa, Kenya. Issue 7 (July 2020) - Islam, Jessica Yasmine; Mutua, Michael M.; Kabare, Emmanuel; Manguro, Griffins; Hudgens, Michael G.; Poole, Charles; Olshan, Andrew F.; Wheeler, Stephanie B.; McClelland, R. Scott; Smith, Jennifer S.
Abstract : Background: Self-collection for high-risk human papillomavirus (hr-HPV) messenger RNA (mRNA) testing may improve cervical cancer screening. High-risk HPV mRNA with self-collected specimens stored dry could enhance feasibility and acceptance of specimen collection and storage; however, its performance is unknown. We compared the performance of hr-HPV mRNA testing with dry- as compared with wet-stored self-collected specimens for detecting high-grade squamous intraepithelial lesion or more severe (≥HSIL). Methods: A total of 400 female sex workers in Kenya participated (2013–2018), of which 50% were HIV positive based on enrollment procedures. Participants provided 2 self-collected specimens: one stored dry (sc-DRY) using a Viba brush (Rovers) and one stored wet (sc-WET) with Aptima media (Hologic) using an Evalyn brush (Rovers). Physician-collected specimens were collected for HPV mRNA testing (Aptima) and conventional cytology. We estimated test characteristics for each hr-HPV screening method using conventional cytology as the reference standard (≥HSIL detection). We also examined participant preference for sc-DRY and sc-WET collection. Results: High-risk HPV mRNA positivity was higher in sc-WET (36.8%) than sc-DRY samples (31.8%). Prevalence of ≥HSIL was 6.9% (10.3% HIV positive, 4.0% HIV negative). Sensitivity of hr-HPV mRNA for detecting ≥HSIL was similar in sc-WET (85%; 95% confidence interval [CI], 66%–96%), sc-DRY specimens (78%; 95% CI, 58%–91%), and physician-collected specimens (93%; 95% CI, 76%–99%). Overall, the specificity of hr-HPV mRNA for ≥HSIL detection was similar when comparing sc-WET with physician collection. However, specificity was lower for sc-WET (66% [61%–71%]) than sc-DRY (71% [66%–76%]). Women preferred sc-DRY specimen collection (46.1%) compared with sc-WET (31.1%). However, more women preferred physician collection (63.9%) compared with self-collection (36.1%). Conclusions: Self-collected stored-dry specimens seemed to perform similarly to sc-WET for the detection of ≥HSIL. Abstract : A study of female sex workers in Mombasa, Kenya, found that self-collected specimens stored-dry performed similarly to specimens stored-wet for human papillomavirus messenger RNA testing to detect high-grade squamous intraepithelial lesions.Supplemental digital content is available in the text.